Strategi Optimalisasi Pengurang Fiskal Dalam Menekan Beban Pajak Penghasilan: Studi PT Indo Kordsa Tbk - Agisti, Chika Almalia; Perwira, Ida Farida Adi; Kustiawan, Memen (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study aims to analyze tax planning as an effort to reduce the income tax payable of PT Indo Kordsa Tbk. The research employs a qualitative approach with a descriptive method through the analysis of secondary data in the form of the company’s 2024 financial statements obtained from the Indonesia Stock Exchange. Data collection techniques were carried out through documentation and literature review to obtain information related to financial reports and tax planning concepts. During the analysis process, several assumptions were also applied due to the unavailability of complete detailed information in the company’s financial statements. The findings indicate that several accounts—such as employee welfare expenses, entertainment and donation expenses, and other operating expenses—can be further optimized through legal and compliant tax planning strategies. The implementation of these strategies succeeded in reducing the income tax burden by 153,302 USD in 2024 and 225,875 USD in 2023, ultimately increasing the company’s profit for the year. This research is expected to be beneficial for companies and practitioners in optimizing fiscal deductions, as well as enriching academic understanding for the development of future studies related to tax planning.